PREVALÊNCIA DE ANEMIA EM GESTANTES ACOMPANHADAS NAS UNIDADES BÁSICAS DE SAÚDE DO MUNICÍPIO DE CARUARU-PE - Weslla Karla Albuquerque Silva de Paula; Elaine Aparecida da Silva Gomes; Islane Carla da Silva (Universidade do Estado do Rio de Janeiro, 2016)
Objective: To assess the prevalence of anemia in pregnant women seen at basic health units in Caruaru, Pernambuco state, Brazil. Methods: A cross-sectional, quantitative study conducted from secondary data drawn from the research information bank entitled "Nutritional status of pregnant women: methodological aspects and epidemiological implications for prenatal screening care." Information in that municipal district was extracted and samples consisted of 141 pregnant women. The data extracted was guided by an instrument containing the variables of interest in the study, involving sociodemographic aspects, obstetric history and data from the current pregnancy. The outcome was considered as anemia Hb <11 mg/dl according to criteria adopted by the World Health Organization. We used Epi-info software 7 to make descriptive and bivariate analyses. Results: Prevalence of anemia was only 5%. Higher frequencies of anemia were observed in pregnant adolescents, with low education, belonging to lower economic classes, who performed just 1-2 antenatal medical consultation visits, starting this monitoring in the 2nd and 3rd quarters and without an antianemic treatment during pregnancy. The bivariate analysis showed no association between the outcome of anemia and evaluated explanatory variables. Conclusion: Research results showed low prevalence of anemia by hemoglobin levels in Caruaru, suggesting the need for further research on factors involving this nutritional deficiency. DOI: 10.12957/demetra.2016.17431